The effects of sweetpotato commercialization on men and women producers and traders in Homa bay and Bungoma, Kenya - Mudege, Netsayi N. (International Potato Center, 2018)
Presented by Nozomi Kawarazuka (CIP), on behalf of Netsayi Mudege, as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.